Sliding mode voltage control strategy for capturing maximum wind energy based on fuzzy logic control. (September 2015) - Yin, Xiu-xing; Lin, Yong-gang; Li, Wei; Gu, Ya-jing; Lei, Peng-fei; Liu, Hong-wei
Highlights: A sliding mode voltage control strategy is proposed to capture the maximum electrical energy from wind. The control strategy mainly includes a fuzzy logic controller and a sliding mode voltage controller. The proposed control strategy can be used to more effectively extract the maximum wind energy as compared with the conventional control method. Abstract: A sliding mode voltage control strategy is proposed in this paper to capture the maximum electrical energy from wind. This control strategy mainly includes a fuzzy logic controller and a sliding mode voltage controller. The fuzzy logic controller is designed to derive the optimum DC-side voltage, while the sliding mode voltage controller is employed to track the derived optimum voltage with minimum steady-state error and hence to capture the maximum wind energy. This paper illustrates how major issues in the design and implementation of the two controllers can be handled effectively. Comparative experimental results demonstrate that significant performance improvements in maximum wind energy capture can be achieved by using the proposed control strategy.